PERAN KELURAHAN TANJUNG SARI KOTA MEDAN DALAM MENINGKATKAN EKONOMI KELUARGA MISKIN MELALUI PROGRAM PEMBERDAYAAN PEREMPUAN DALAM UPAYA PENINGKATAN PENDAPATAN KELUARGA (UP2K) - Aprillia, Putri (Al-Iqtisodiyah : Jurnal Ilmu Ekonomi dan Ekonomi Islam, 2025)
The Family Income Improvement Program (UP2K) in Tanjung Sari Village has been running for approximately ten years, but its implementation has not been optimal due to weak program management by the village administration. This study aims to analyze the implementation of the UP2K Program using a descriptive method with a qualitative approach. Data were collected through interviews, observations, and documentation studies, and analyzed using the theory of the main roles of the public sector according to (Jones, 1993) in (Mahsun, 2006), which includes regulatory roles, enabling roles, and directing roles. The results of the study indicate that the UP2K Program has had a positive impact on increasing the income and welfare of the beneficiary community, although the effect is not yet significant. The program is also considered to be on target in supporting family economics, which has the potential to improve community health, education, and skills. However, overall, the implementation of the UP2K Program in Tanjung Sari Village is still not running well and requires managerial strengthening from the village administration.